Circulating CXCR5+CD4+helper T cells in systemic lupus erythematosus patients share phenotypic properties with germinal center follicular helper T cells and promote antibody production. (August 2015) - Zhang, X; Lindwall, E; Gauthier, C; Lyman, J; Spencer, N; Alarakhia, A; Fraser, A; Ing, S; Chen, M; Webb-Detiege, T; Zakem, J; Davis, W; et al.
Objective: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of autoantibodies. Recently, a specific highly activated T helper cell subset, follicular helper T (Tfh) cell, has emerged as a key immunoregulator of germinal center (GC) formation and high-affinity antibody production. To identify the pathophysiological role of Tfh cells in SLE patients, we compared the phenotypic and functional properties of circulating Tfh-like cells in lupus patients to GC-Tfh cells, and correlated the percentage of Tfh-like cells with autoantibody production and SLE disease activity. Methods: Peripheral blood was collected from 29 lupus patients and 25 healthy controls. Tonsils were obtained surgically from non-SLE controls and used as a source of GC-Tfh cells. Tfh cells were defined by their signature surface markers (CXCR5, ICOS, CD57, PD-1 and BTLA) via flow cytometry. IL-21 expression levels from Tfh cells were measured by real-time PCR and intracellular staining. The function of Tfh cells was carried out by co-culture of Tfh cells and autologous B cells in vitro . IgG in the culture supernatant was detected by ELISA. Results: The frequency of circulating Tfh-like cells was significantly increased in SLE patients compared to healthy controls ( p < 0.05). The Tfh-like cells not only display similar phenotypes and signature cytokines with GC-Tfh cells, but also are capable of driving B cells to differentiate into IgG-secreting plasma cells in vitro . In addition, the frequency of Tfh-like cells correlated positively with the percentage of circulating plasmablasts, levels of serum anti-dsDNA antibodies and ANA. Conclusion: The accumulated circulating Tfh-like cells in lupus patients share phenotypic and functional properties with GC-Tfh cells. Tfh-like cells may serve as perpetuators in the pathogenesis of SLE by enhancing the self-reactive B cell clones to further differentiate into auto antibody-producing plasmablasts, and ultimately cause autoimmunity.